Improved gravitational search algorithm for proportional integral derivative controller tuning in process control system - Aziz, Mohamad Saiful Islam (2016)
Proportional-Integral-Derivative (PID) controller is one of the most used controllers in the industry due to the reliability and simplicity of its structure. However, despite its simple structure controller, the tuning process of PID controller for nonlinear, high-order and complex plant is difficult and faces lots of challenges. Conventional method such as Ziegler-Nichols are still being used for PID tuning process despite its lack of tuning accuracy. Nowadays researchers around the world shift their attention from conventional method to optimisation-based methods. For the last five years, optimisation techniques become one of the most popular methods used for tuning process of PID controller. Optimisation techniques such as Genetic Algorithm (GA), Particle Swarm Optimisation (PSO) as well as Gravitational Search Algorithm (GSA) are widely used for the PID controller application. Despite the effectiveness of GSA for PID controller tuning process compared to the GA and PSO technique, there is still a room for improvement of GSA performance for PID controller tuning process. This research represents the additional characters in GSA to enhance the PID controller parameter tuning performance which are Linear Weight Summation (LWS) and alpha parameter range tuning. Performance of optimisation-based PID controllers are measured based on the transient response performance specification (i.e. rise time, settling time, and percentage overshoot). By implementing these two approaches, results show that Improved Gravitational Search Algorithm (IGSA) based PID controller produced 20% to 30% faster rise and settling time and 25% to 35% smaller percentage overshoot compared to GA-PID and PSO-PID. For real implementation analysis, IGSA based PID controller also produced faster settling time and lower percentage overshoot than other optimisation-based PID controller. A good controller viewed as a controller that produced a stable dynamic system. Therefore, by producing a good transient response, IGSA based PID controller is able to provide a stable dynamic system performance compared to other controllers.